The Role of Digital Transformation in Stabilizing Business Cycles Post-COVID-19 - Sule, Sani Abdullahi; Hakim, Lukman; Putro , Tetuko Rawidyo; Pamungkas, Putra (SSD Journal, 2025)
The COVID-19 pandemic disrupted global economies, highlighting vulnerabilities in traditional business models and driving an urgent need for digital transformation. This paper explores the role of digital technologies in stabilizing business cycles during the post-pandemic recovery. The objectives are to assess how innovations like artificial intelligence, cloud computing, and big data analytics helped industries manage uncertainty, enabled governments to implement effective recovery policies, and facilitated workforce adaptability in the new normal. Key findings indicate that digital tools significantly transformed sectors such as supply chains, retail, healthcare, and workforce dynamics, enhancing flexibility and resilience during economic shocks. The theoretical implications extend Schumpeter’s innovation theory, applying it to the digital age to demonstrate how innovation can stabilize economies. Empirically, the study provides actionable insights for policymakers, recommending investments in digital infrastructure, the promotion of scalable digital solutions in businesses, and the integration of digital literacy in educational curricula. Future research should examine the long-term impacts of digital transformation on business cycle stability, explore regional variations in digital adoption, and investigate the role of emerging technologies like blockchain and quantum computing in economic resilience.